The Fair and Wise King behind the Sacred Myth of Puak Reflected the Leader Horizon Representation of Kampong Tua Malay Nongsa: Ethnoecological Approach - Arianto, Tomi; Suryani, Melly Siska (TONIL: Jurnal Kajian Sastra, Teater dan Sinema, 2020)
Longing for a just and wise leader built a horizon of hope for society behind the mythical stories of the king of dreams. Like the fringe warriors in Javanese society, the Malays in Kampong Tua Nongsa have a role model king known as The King of Fuang. This study aimed to reveal the theme of ethnoecology in the Malay community behind the mythical story of Puak sacred in Nongsa, a Batam district. The ethnoecology approach connected a community paradigm that is formed due to natural phenomena. The interaction between humans and nature through the sacred existence of Puak was created by the role model of the king. This study used a qualitative descriptive method with observation data collection techniques and in-depth interviews. Analytical criticism techniques become a meant to reveal the ethnoecology behind the story. The results of this research show that there are two important things to discuss, namely the representation of the just king and cultural products from nature in the form of prohibitions. A king who is a role model for the hope of a community leader in the form of a king who is honest and keeps his promises, a king who does not want to be exalted and exalted, a king who is just and wise, a king who is simple, a king who protects and preserves nature. Meanwhile, the resulting cultural products are in the form of prohibitions on destroying forests, prohibitions on cutting hills, prohibitions on lying, prohibitions on speaking arrogantly, prohibitions on speaking dirty, and prohibitions on wasting wealth.